Tradisi Hepatirangga pada Orang Wanci di Kelurahan Pongo Kecamatan Wangi-Wangi Kabupaten Wakatobi - Dessiria; La Niampe; Rahmat Sewa Suraya (Jurusan Tradisi Lisan, Fakultas Ilmu Budaya, Univeritas Halu Oleo, 2023)
The Hepatirangga tradition is a tradition on the night of lailatul qadar or the twenty-seventh night (27th) until the night of Eid where to produce a redder color. The implementation of hepatirangga is carried out at night so that the results are better. Location of Pongo Village, Wangi-Wangi District, Wakatobi Regency. Data collection techniques were carried out by direct observation, interviews with informants and documention. Determination of informants using purposive sampling. Data analysis used descriptive qualitative analysis by covering data collection, data reduction, data presentation, and drawing conclusions. The results of the study show that the process of implementing the hepatirangga tradition consists of several stages of implementation, namely equipment. The purpose of the equipment stage is to emphasize the equipment and materials related to the tradition being carried out. equipment, tools and materials referred to here are very important and must be met during implementation. hepatirangga so that this tradition is carried out. The tools and materials referred to here are knives or scissors, raffia rope, wheel leaves or plastic bags, blender or mortar, and patirangga leaves. The implementation stage, in the implementation of the hepatirangga tradition, is carried out at night. The final stage is after all the processes are complete, then leave it overnight and open it at dawn. The meaning contained in the hepatirangga tradition is the meaning of letting go of patirangga before dawn, tightening kinship ties, as a connecting medium with ancestors such as beauty/aesthetics, solidarity values (togetherness), and religious cultural values.